Implementation of Sugar-Sweetened Beverages Excise Policy and Its Implications in Various Countries: Literature Review - Khotami, Roissiana; Yulianty, Vetty; Oktarina, Ratih (UI Scholars Hub, 2024)
The prevalence of diabetes in the world is projected to continue to increase to 643 million in 2030. Indonesia is ranked 7th with the highest number of diabetes mellitus sufferers and the only one in Southeast Asia with a total of 10.7 million sufferers. Consumption of sweetened drinks is the most dominant factor in the incidence of diabetes mellitus in Indonesia. Indonesia ranks third highest in Southeast Asia in sweetened drink consumption. Excise on sweetened drinks is an effective intervention to reduce consumption of sweetened drinks, but Indonesia has not yet implemented it. This research aims to determine the implementation of excise tax policies on sweetened drinks and their implications in various countries. The study used a literature review using PubMed, ScienceDirect, Springer Link, and Scopus online databases and was based on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis). Fifteen articles were analyzed in this study. The study was conducted in Chile, Mexico, Berkeley, San Francisco, Portugal, Germany, Ireland, the UK, South Africa, Zambia, Thailand, and Saudi Arabia while the articles were published in 2013-2021. The conclusion is excise tariffs are carried out with a specific system and ad valorem. The excise policy on sweetened drinks can lead to reduced consumption, energy intake, and the prevalence of non-communicable diseases so that it can reduce healthcare costs. From an economic standpoint, it impacts increasing state revenues, does not affect job losses, and creates industrial resistance.